PI controller for DC motor speed realized with simulink and practical measurements - Mohammed A. Ibrahim; Ali N. Hamoodi; Bashar M. Salih (Institute of Advanced Engineering and Science, 2020)
This article describes the methodology of speed control by understanding control method of DC motor, definitely, armature and field resistances with additional to armature voltage control methods. The speed of DC motor is controlled PI controller as donor in this work. Using Matlab simulation and practical measurements, Terco DC motor speed control is achieved in this work. The results that obtained from Matlab simulation circuit is appeared approximately similar that obtained by practical connection.